INCIDENCE AND EXPERIMENTAL INFECTION OF CRYPTOSPORIDIUM BAILEYI IN CHICKEN - & et al., AL-Zubaidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to investigate the incidence of Cryptosporidiosis in 200 fecal samples from slaughtered broiler chicken carcasses in the local markets in some areas of Baghdad city (Al-Hurriya, Al -Kadhimiya and Al-Shuala), during March to May 2017. Three diagnostic techniques used (flotation by Sheather's sugar solution, staining with Modified Zeihl-Neelsen stain, and measuring of isolated Cryptosporidium oocysts by ocular micrometer) to determine the type of Cryptosporidium species, and for conform that the isolated species of parasite from infected cases belong to the C.baileyi.  Experimental infection done in, 18 broiler chicken chicks aged one week divided to three groups first (G1) and second (G2) inoculated orally with, (500, 1000) oocysts per chick respectively, while the third group remain as a control (G3), than pathological lesions detected in some internal organs of infected chicks (trachea, intestine and bursa of fabricius). The study recorded a total infection rate 35% (75/200) in slaughtered broiler chicken. The result were revealed that the highest rate of infection occurs in April, reached 46% (23/50), while the lowest rate of infection in June, reached 20% (10/50). The experimental study revealed, the infection was occur in all chicks, of (G1) and (G2), and the first clinical signs appear after 7days post infection (PI) which include diarrhea, dullness, anorexia, and increased consumption of water, which represented the incubation period of the parasite, while the shedding of oocysts  in feces started after 6-9days PI.